The policy of permeation of Fabian Society into the National Health Service policy of Labour Party in the early 20th century - Wang Zixuan (SHS Web of Conferences, 2024)
In pursuit of social reform, Fabian Society, a British Socialist Group, adopted the a policy of permeation of other parties. Under the influence of osmosis, Fabian Society, represented by Mr and Mrs Webb, exerted influence over Labour’s policy on the National Health Service, and in the continuous run-in to the national health service in part of the Labour policy and views with Fabian Society gradually convergence. By drawing on the positive experience of Fabian, combining the establishment of a jointly managed health system, the consolidation of redundant health services, the improvement of the administrative efficiency of government-related services, the development of voluntary hospitals and sanatoriums with the inherent commitment of the Labour Party to free health care for all, and the establishment of a public health sector at the national level, thus for the UK in the field of public health to establish a national medical social system to provide an excellent blueprint. Labour’s policies in the field of national health have profoundly changed the face of British society.